Expected Return on Activities and Changes in Dental Care with COVID-19 - Josué Júnior Araújo Pierote; Renato Assis Machado; João Victor Frazão Câmara; Luiz Alexandre Maffei Sartinni Paulillo (Association of Support to Oral Health Research (APESB), 2021)
Dear Editor, The novel coronavirus (COVID-19) has been spreading daily all over the world. Currently, more than 17,106,007 cases were positive for COVID-19 worldwide and 668,910 deaths (https://who.sprinklr.com). Besides that, few is known about this virus and what the real damage it can cause. The COVID-19 was identified in the saliva of infected patients, and this fluid can be pivotal in the transmission between humans. As a thought for dental clinics, many droplets and aerosols from saliva are expected, so that dental schools were closed, and dental clinics have been advised to maintain only urgency services around the world. However, even after returning from activities, we will need to be very careful. Analysis of the Covid-19 transmission projections will possibly require intermittent or prolonged isolation and social distancing measures until 2022 in the absence of an effective preventive measure. Even in periods of apparent pandemic control, monitoring must be maintained since the risk of a resurgence of new waves of spread and contamination may be possible until 2024 [1].